Developing an Effective Marketing Strategy for Traditional Herbal Medicine: A Strategic Approach Based on Qualitative Insights - Putri Septia Ningsih; Reza Reza; Indah Permatasari; Ratna Fitri Astuti (Journal of Economic Education and Entrepreneurship Studies, 2025)
Traditional herbal medicine businesses often face significant challenges in effectively reaching their target markets, particularly due to limitations in marketing capabilities. This study investigates the marketing strategies employed by a traditional herbal medicine enterprise that has operated for seven years but continues to experience limited market penetration and promotional effectiveness. The research aims to identify the current marketing practices and explore strategic approaches to enhance product appeal and expand consumer reach across diverse demographic groups. Employing a qualitative descriptive method, data were collected through in-depth interviews and field observations involving nine informants, including the business owner, employees, and consumers. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing/verification. The findings reveal that the enterprise's marketing strategy comprises consumer segmentation, product development, pricing, distribution, and promotional activities. The primary customer segment ranges from 25 to 50 years of age, typically with a habitual consumption of herbal medicine. The business emphasizes product variety, practical and hygienic packaging, and quality assurance. Pricing strategies are aligned with perceived value and product benefits. Effective distributor and supplier communication supports consistent promotional efforts. Offline promotional methods such as bazaars and exhibitions were found to be more successful in engaging customers compared to social media outreach. This study highlights the need for tailored marketing strategies that leverage both traditional and digital channels to optimize market reach for traditional herbal medicine products.